Analisis Implementasi Manajemen Risiko pada UMKM Fotocopy Cipta Warna Panyileukan - Nabila, Afifa; Nur Fadila, Aulia (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This study analyzes the implementation of risk management in UMKM Fotocopy Cipta Warna, Panyileukan, with the aim of identifying the types of risks faced and disseminating the mitigation measures taken. A qualitative approach was used through direct interviews with business owners. The main findings showed several key risks, such as financial risks due to the COVID-19 pandemic causing a decrease in revenue, operational risks related to photocopier maintenance, and market risks due to digitalization and changing customer needs. On the other hand, although there are many similar businesses around the location, the owner does not feel there is significant competition. Based on the analysis, it is recommended that the business improve financial recording with a structured accounting system and develop innovative marketing strategies to attract more customers in the digital era.